2015
DOI: 10.1097/wno.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Phosphodiesterase-5 Inhibitors and Nonarteritic Anterior Ischemic Optic Neuropathy

Abstract: Our results do not suggest any association between having a prescription filled for PDE-5 inhibitor medication and receiving a diagnosis code for NAION. This is consistent with other studies in the literature that have failed to elucidate a plausible mechanism by which these drugs might compromise circulation at the optic nerve head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…11 In an analysis by Pomeranz 12 of data on adverse events from the FDA, reports of ischemic optic neuropathy associated with PDE5-I use were more numerous than the number of cases from the published literature. However, some previous articles also reported no significant association between NAION and PDE5-I use 13 , 14 and the causality between them could not be elucidated clearly in current publications. Therefore, we conducted a systematic review and meta-analysis to investigate their association through combined statistics to provide some further evidence for the occurrence of NAION and rational use of PDE5-Is.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…11 In an analysis by Pomeranz 12 of data on adverse events from the FDA, reports of ischemic optic neuropathy associated with PDE5-I use were more numerous than the number of cases from the published literature. However, some previous articles also reported no significant association between NAION and PDE5-I use 13 , 14 and the causality between them could not be elucidated clearly in current publications. Therefore, we conducted a systematic review and meta-analysis to investigate their association through combined statistics to provide some further evidence for the occurrence of NAION and rational use of PDE5-Is.…”
Section: Introductionmentioning
confidence: 63%
“…A flowchart of the screening process of the meta-analysis is presented in Figure 1 . Of the 5 studies, 1 was a prospective case-crossover study, 19 1 was a retrospective case-crossover study, 12 1 was a retrospective case-control study, 13 and 2 were retrospective cohort studies. 14 , 20 The study by Flahavan et al 19 was conducted mostly in Caucasians in the United Kingdom, and the others were conducted in mixed populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, anterior ischemic neuropathy has been reported in association with PDE-5 inhibitor (e.g., sildenafil, vardenafil, and tadalafil) use. Relative afferent pupillary defect, decreased color vision, and visual field defect indicate this type of neuropathy (9,10). Recently, Zahavi et al (11) demonstrated that sildenafil may induce ischemic retinal changes in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, a large retrospective cohort study involving 4 157 357 male veterans found no increased risk of NAION in men prescribed PDE‐5 inhibitors [odds ratio 1.02 (95% confidence interval 0.92–1.12)] . Similar findings using administrative data have continued to accumulate, despite anecdotal reports of the close temporal relationships between drug exposure and vision loss . One pharmaceutical company conducted its own prospective study and found a twofold increased risk of NAION within five half‐lives of PDE‐5 inhibitor use, a hazard that translates to three additional cases of NAION per 100 000 men 50 years of age and older each year .…”
mentioning
confidence: 99%